Influence of Mindfulness Techniques on Reducing Academic Stress and Enhancing Students' Concentration in Learning - Dina Hidayati Hutasuhut; Dinda Yarshal (International Journal of Educational Development, 2025)
This study examines the effect of mindfulness techniques on reducing academic stress and increasing concentration in students. With increasing academic demands, many students experience stress that interferes with the learning process. Mindfulness techniques, which emphasize full awareness, have been shown to be effective in reducing anxiety and improving mental well-being. The experimental method involved two groups of students: one group implemented mindfulness techniques, while the control group received no intervention. Data were collected through questionnaires measuring levels of academic stress and concentration before and after the intervention. The results indicated that the group practicing mindfulness experienced a significant decrease in stress and an increase in concentration compared to the control group. These findings support the use of mindfulness techniques as an effective strategy to help students and recommend their integration into higher education curricula for academic well-being.